2011
DOI: 10.1002/jqs.1465
|View full text |Cite
|
Sign up to set email alerts
|

The last deglacial history of Lützow‐Holm Bay, East Antarctica

Abstract: Past fluctuations of the Antarctic ice sheet are poorly understood because of a lack of datable materials, radiocarbon reservoir ages and severe environments. Direct evidence of the timing of ice retreat is important in order to understand the Antarctic contribution to global sea-level rise since the Last Glacial Maximum. Here we report the first exposure ages constraining the timing of the last deglaciation from Lü tzow-Holm Bay, East Antarctica. Our data suggest that the final retreat of the ice sheet in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 28 publications
1
19
0
2
Order By: Relevance
“…Observations and interpretations of these bedforms have been used to reconstruct the historical development of glacial erosional bedforms (e.g., Shaw 2002), and to understand the significance and implications of subglacial water-rock interactions. Further support for this finding comes from the cosmogenic radionuclide dating of local glacial erratics and bedrock (Yamane et al 2011). Both bedrocks and erratics show similar exposure ages, suggesting the presence of warm basal ice during the last glacial period, which would have included subglacial water channels.…”
Section: Primary Producers and Estimates Of Biogenic Silicamentioning
confidence: 82%
See 1 more Smart Citation
“…Observations and interpretations of these bedforms have been used to reconstruct the historical development of glacial erosional bedforms (e.g., Shaw 2002), and to understand the significance and implications of subglacial water-rock interactions. Further support for this finding comes from the cosmogenic radionuclide dating of local glacial erratics and bedrock (Yamane et al 2011). Both bedrocks and erratics show similar exposure ages, suggesting the presence of warm basal ice during the last glacial period, which would have included subglacial water channels.…”
Section: Primary Producers and Estimates Of Biogenic Silicamentioning
confidence: 82%
“…Cosmogenic-radionuclide-based dating of raised beach exposures showed that Holocene deglaciation occurred locally on the Soya Coast at ca. 10 ka (Yamane et al 2011). Bassett et al (2007) also compared predictive models of glacio-isostatically induced relative sea-level changes at seven other locations around the Antarctic coast, as well as on the Soya Coast.…”
Section: Geological Setting Of the Sampling Sitesmentioning
confidence: 99%
“…The timing of the remainder of the ice lowering to the present ice surface elevation at this site (~ 150 m asl) is less clear, as we did not observe any moraines or trimlines below CHL that would indicate any significant stillstands or readvances during the retreat from CHL to the modern ice surface. Regardless, the early Holocene timing and magnitude of ice elevation lowering along the lower Rayner Glacier is very similar to that measured near the modern grounding line at the Framnes Mountains [ Mackintosh et al ., ], where ~ 350 m was lost between 12 and 6 ka, and also Lutzow‐Holm Bay, where ~ 350 m of ice was lost between 10 and 6 ka [ Yamane et al ., ]. The synchronicity of ice retreat at sites in similar glaciological positions along their ice drainages to the east and west flags the possibility that this event may have been regional in extent.…”
Section: Discussionmentioning
confidence: 99%
“…The source of meltwater is likely to be from Antarctica because the Laurentide ice sheet had largely melted by 6 ka (Carlson et al, 2008;Shiorya et al, 2013). Geological and geochemical RSL evidence from sites proximal to Antarctica indicate that ice sheet size decreased during the Holocene (Yamane et al, 2011;Takano et al, 2012). This is accompanied by southern ocean environmental changes including migrations of the polar front and surface ocean warming (Katsuki et al, 2012;Ijiri et al, 2014;Yamane et al, 2014).…”
Section: Data-model Comparison and Holocene Melting Of Antarctic Ice mentioning
confidence: 94%